Dynamic stress-strain state of a single-section manipulator - Arinov, Е.; Karipbaev, S.Zh.; Sartayev, K.Z. (Bulletin of the Karaganda University. Mathematics Series, 2017)
The dynamics of elastically deformed plane and spatial mechanisms is modeled. Matrices are constructed that describe the inertial, dissipative, and stiffness properties of elements under the action of external forces, inertia forces, additional nodal forces. The total displacements are described by the sum of deformation and kinematic displacements. An algorithm and a complex of a computational package of applied programs are developed on the basis of the developed approaches, Methodical basis for multivariate computer calculations of forces, dynamic stress - strain state in the elements of elastic mechanisms. The finite element method used in the work makes it possible for multivariate calculations of the stress - strain state of the mechanisms, To establish the regularity of the distribution of elastic displacements, internal forces, stresses, depending on numerous factors: Elastic properties, motion parameters, external static and time - varying forces.